2016
DOI: 10.1016/j.jhazmat.2016.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive photoelectrochemical determination of chromium(VI) in water samples by ion-imprinted/formate anion-incorporated graphitic carbon nitride nanostructured hybrid

Abstract: A rapid and highly sensitive photoelectrochemical (PEC) method has been proposed for the determination of trace amounts of chromium in water samples under visible-light irradiation. Here, a unique nanostructured hybrid of formate anion incorporated graphitic carbon nitride (F-g-C3N4) is smartly integrated with a Cr(VI) ion-imprinted polymer (IIP) as a photoactive electrode (denoted as IIP@F-g-C3N4). The nanohybrid of F-g-C3N4 exhibits an enhanced charge separation with substantially improved PEC responses vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…with a Cr 6+ -imprinted polymer (IIP) (IIP@F-g-C 3 N 4 ). [59] Compared with g-C 3 N 4 , the nanocomposite exhibits enhanced charge separation and substantially improved PEC responses. The results prove that the IIP@F-g-C 3 N 4 PEC sensor offers high sensitivity and selectivity for the detection of Cr 6+ , and IIP@F-g-C 3 N 4 analysis provides competent photogenerated electrons for the reduction of Cr 6+ (Figure 2g).…”
Section: Fang Et Al Reported a Nanocomposite Of Formatted Anionmentioning
confidence: 99%
See 1 more Smart Citation
“…with a Cr 6+ -imprinted polymer (IIP) (IIP@F-g-C 3 N 4 ). [59] Compared with g-C 3 N 4 , the nanocomposite exhibits enhanced charge separation and substantially improved PEC responses. The results prove that the IIP@F-g-C 3 N 4 PEC sensor offers high sensitivity and selectivity for the detection of Cr 6+ , and IIP@F-g-C 3 N 4 analysis provides competent photogenerated electrons for the reduction of Cr 6+ (Figure 2g).…”
Section: Fang Et Al Reported a Nanocomposite Of Formatted Anionmentioning
confidence: 99%
“…[63] Copyright 2016, Royal Society of Chemistry; (g) Reproduced with permission. [59] Copyright 2016, Elsevier B.V.; (h) Reproduced with permission. [61] Copyright 2017, Elsevier B.V.; (i, j) Reproduced with permission.…”
Section: Fang Et Al Reported a Nanocomposite Of Formatted Anionmentioning
confidence: 99%
“…A nanostructured photoelectrochemical sensing element based on the use of Cr(VI) ion imprinted polymer and formate ion incorporated graphitic carbon nitride has been explored by the Tian Fang group [ 78 ] for Cr(VI) measurement in different water samples with good recovery of 89.8–105% at 0.006 µg·L −1 . The designed sensor exhibits high selectivity and sensitivity towards Cr(VI) owing to the efficient photogenerated electron reduction offered toward Cr(VI).…”
Section: Electrochemical Sensors For Hexavalent Chromium Determinamentioning
confidence: 99%
“…In another study, a PEC sensor based upon the combination of Cr(VI) ion imprinted polymer and formate anion incorporated graphitic carbon nitride (IIP@F-g-C 3 N 4 ) was developed and destined to Cr(VI) detection. The constructed sensor could also be used for total chromium quantification and that after the oxidation of Cr(III) by the use of hydrogen peroxide (H 2 O 2 ) whereas Cr(III) content was calculated by subtracting the Cr(VI) concentration from total Cr [ 78 ]. Another research group has developed a specific sensor for chromium determination at ppt level [ 43 ].…”
Section: Sensors and Biosensors-based Chromium Speciationmentioning
confidence: 99%
“…In 1972, Wulff et al 17 proposed molecule imprinting polymers, which have been shown to be an effective way to remove heavy metal ions from industrial wastewater with good selectivity. [18][19][20] Furthermore, the surface ion imprinting polymer technology (IIP) was studied because the traditional IIP have innate limitations such as heterogeneous distribution of the binding sites, incomplete template removal, and slow mass transfer for the target ions. Until now, numerous IIP studies have focused on Cr(VI) adsorption.…”
Section: Introductionmentioning
confidence: 99%